Patient and service factors associated with referral and admission to inpatient rehabilitation after the acute phase of stroke in Australia and Norway - Angela S. Labberton; Mathias Barra; Ole Morten Rønning; Bente Thommessen; Leonid Churilov; Dominique A. Cadilhac; Elizabeth A. Lynch (BMC, 2019)
Abstract Background Unequal access to inpatient rehabilitation after stroke has been reported. We sought to identify and compare patient and service factors associated with referral and admission to an inpatient rehabilitation facility (IRF) after acute hospital care for stroke in two countries with publicly-funded healthcare. Methods We compared two cohorts of stroke patients admitted consecutively to eight acute public hospitals in Australia in 2013-2014 (n = 553), and to one large university hospital in Norway in 2012-2013 (n = 723). Outcomes were: referral to an IRF; admission to an IRF if referred. Logistic regression models were used to identify and compare factors associated with each outcome. Results Participants were similar in both cohorts: mean age 73 years, 40-44% female, 12-13% intracerebral haemorrhage, ~ 77% mild stroke (National Institutes of Health Stroke Scale < 8). Services received during the acute admission differed (Australia vs. Norway): stroke unit treatment 82% vs. 97%, physiotherapy 93% vs. 79%, occupational therapy 83% vs. 77%, speech therapy 78% vs. 13%. Proportions referred to an IRF were: 48% (Australia) and 37% (Norway); proportions admitted: 35% (Australia) and 28% (Norway). Factors associated with referral in both countries were: moderately severe stroke, receiving stroke unit treatment or allied health assessments during the acute admission, living in the community, and independent pre-stroke mobility. Directions of associations were mostly congruent; however younger patients were more likely to be referred and admitted in Norway only. Models for admission among patients referred identified few associated factors suggesting that additional factors were important for this stage of the process. Conclusions Similar factors were associated with referral to inpatient rehabilitation after acute stroke in both countries, despite differing service provision and access rates. Assuming it is not feasible to provide inpatient rehabilitation to all patients following stroke, the criteria for the selection of candidates need to be understood to address unwanted biases.